Polydiacetylene (PDA) Embedded Polymer-Based Network Structure for Biosensor Applications - Huisoo Jang; Junhyeon Jeon; Mingyeong Shin; Geonha Kang; Hyunil Ryu; Sun Min Kim; Tae-Joon Jeon (Gels, 2025)
Biosensors, which combine physical transducers with biorecognition elements, have seen significant advancement due to the heightened interest in rapid diagnostic technologies across a number of fields, including medical diagnostics, environmental monitoring, and food safety. In particular, polydiacetylene (PDA) is gaining attention as an ideal material for label-free colorimetric biosensor development due to its unique color-changing properties in response to external stimuli. PDA forms through the self-assembly of diacetylene monomers, with color change occurring as its conjugated backbone twists in response to stimuli such as temperature, pH, and chemical interactions. This color change enables the detection of biomarkers, metal ions, and toxic compounds. Moreover, the combination of PDA with polymeric structures including hydrogels further enhances the sensitivity and structural stability of PDA-based biosensors, making them reliable and effective in complex biological and environmental conditions. This review comprehensively examines recent research trends and applications of PDA–polymeric structure hybrid biosensors, while discussing future directions and potential advancements in this field.